Ca/Ti ratio of sediment core D11956TC/P - Susana Martin Lebreiro; Laura Antón; Isabel Reguera; Rocio Lozano (PANGAEA, 2025)
The Ca and Ti of core D11956T/P from the Tagus Abyssal Plain were measured at a resolution of 2 mm, performed at BOSCORF, Southampton National Center, U.K., using a COX Analytical Systems Itrax X-ray Fluorescence (XRF) scanner, and the data processed with the included bAxil software. The elements considered here (Ca, Ti) were extracted from a series of 15 (10 kV), 17 (30 kV) and 7 (50 kV) elements.